MELTING OF BIOTITE + PLAGIOCLASE + QUARTZ GNEISSES: THE ROLE OF H2O IN THE STABILITY OF AMPHIBOLE - Gardien V.; Thompson A.B.; Ulmer P. (My University, 2000)
Biotite + plagioclase + quartz (BPQ) is a common assemblage in gneisses, metasediments and metamorphosed granitic to granodioritic intrusions. Melting experiments on an assemblage consisting of 24 vol. % quartz, 25 vol. % biotite (XMg = 0·38–0·40), 42 vol. % plagioclase (An26–29), 9 vol. % alkali feldspar and minor apatite, titanite and epidote were conducted at 10, 15 and 20 kbar between 800 and 900°C under fluid-absent conditions and with small amounts (2 and 4 wt %) of water added to the system. At 10 kbar when 4 wt % of water was added to the system the biotite melting reaction occurred below 800°C and produced garnet + amphibole + melt. At 15 kbar the melting reaction produced garnet + amphibole + melt with 2 wt % added water. At 20 kbar the amphibole occurred only at high temperature (900°C) and with 4 wt % added water. In this last case the melting reaction produced amphibole + clinopyroxene ± garnet + melt. Under fluid-absent conditions the melting reaction produced garnet + plagioclase II + melt and left behind a plagioclase I ± quartz residuum, with an increase in the modal amount of garnet with increasing pressure. The results show that it is not possible to generate hornblende in such compositions without the addition of at least 2–4 wt % H2O. This reflects the fact that conditions of low aH2O may prevent hornblende from being produced with peraluminous granitic liquids from the melting of biotite gneiss. Thus growth of hornblende in anatectic BPQ gneisses is an indication of addition of external H2O-rich fluids during the partial melting event.